A Soft Corner Approach to Think/Act for Conservation Defining Wildlife Conservation and Law Enforcement Initiatives of Nepal Police - Subedi, Devendra (The Initiation, 2010)
DOI: 10.3126/init.v1i0.2687 The Initiation Vol.1 2007 p.84-87